2015
DOI: 10.1161/atvbaha.115.305609
|View full text |Cite
|
Sign up to set email alerts
|

Foamy Monocytes Form Early and Contribute to Nascent Atherosclerosis in Mice With Hypercholesterolemia

Abstract: Objective To examine infiltration of blood foamy monocytes, containing intracellular lipid droplets, into early atherosclerotic lesions and its contribution to development of nascent atherosclerosis. Approach and Results In apoE−/− mice fed western high-fat diet (WD), >10% of circulating monocytes became foamy monocytes at 3 days on WD and >20% of monocytes at 1 week. Foamy monocytes also formed early in blood of Ldlr−/−Apobec1−/− (LDb) mice on WD. Based on CD11c and CD36, mouse monocytes were categorized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
123
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(144 citation statements)
references
References 42 publications
(97 reference statements)
12
123
2
7
Order By: Relevance
“…While the role of circulating monocytes as precursors of macrophages, which after moving to the subendothelial space become foam cells, is clearly defined (Moore and Tabas, 2011;Tabas and Bornfeldt, 2016), our previous results support the emerging paradigm that monocytes interacting with proinflammatory products released by endothelial cells may acquire a foamy phenotype well before they cross the endothelial layer and differentiate into macrophages (Wu et al, 2009;Foster et al, 2015;Robbins et al, 2013;Xu et al, 2015). The accumulation of lipid droplets in the monocytes is accompanied by increased expression of adhesion and chemokine receptors and overall proinflammatory markers, resulting in a higher risk of cardiovascular disease.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…While the role of circulating monocytes as precursors of macrophages, which after moving to the subendothelial space become foam cells, is clearly defined (Moore and Tabas, 2011;Tabas and Bornfeldt, 2016), our previous results support the emerging paradigm that monocytes interacting with proinflammatory products released by endothelial cells may acquire a foamy phenotype well before they cross the endothelial layer and differentiate into macrophages (Wu et al, 2009;Foster et al, 2015;Robbins et al, 2013;Xu et al, 2015). The accumulation of lipid droplets in the monocytes is accompanied by increased expression of adhesion and chemokine receptors and overall proinflammatory markers, resulting in a higher risk of cardiovascular disease.…”
Section: Introductionsupporting
confidence: 76%
“…The accumulation of lipid droplets in the monocytes is accompanied by increased expression of adhesion and chemokine receptors and overall proinflammatory markers, resulting in a higher risk of cardiovascular disease. Thus lipid droplets in circulating monocytes are being considered not only a possible therapeutic target, but also a marker of risk (Wu et al, 2009;Foster et al, 2015;Robbins et al, 2013;Xu et al, 2015). In this regard, our molecular analysis of the fatty acid composition of the neutral lipids of foamy monocytes revealed their selective enrichment in a relatively minor fatty acid, identified as palmitoleic acid (Guijas et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
“…In another publication, the same research group reported that monocytes from patients with familial dysbetalipoproteinaemia (FD) also had increased intracellular lipid accumulation and higher expression of surface β 2 -integrins, including integrin-α M (CD11b), integrin-α X (CD11c), and integrin-β 2 (CD18) 5 . These observations support an important role of intracellular lipid accumulation in monocyte phenotypic changes in patients with FH or FD, and are consistent with previous reports from our laboratory and others showing emergence of monocytes with intracellular lipid droplets, which we termed ‘foamy monocytes’, and monocyte phenotypic changes including increased levels of integrin-α X in the circulation of humans and animals with hyperlipidaemia 69 . Foamy monocytes emerge early in the circulation of mice with hypercholesterolaemia 6 .…”
supporting
confidence: 92%
“…Monocyte lipid uptake is dependent on CD36 and is associated with upregulated expression of CD11c, chemokine receptors, and activation of CD49d (α4) integrin, which mediates adhesion to vascular cell adhesion molecule-1. [138][139][140][141] Monocytes with cytoplasmic lipid droplets can also be found in humans after a high-fat high-cholesterol meal, but the extent of intracellular lipid is much lower relative to mice. 139,140,142,143 The systemic effects of hyperlipidemia on circulating monocytes promote monocyte recruitment to atherosclerotic lesions.…”
mentioning
confidence: 99%